2013 IEEE International Conference on Acoustics, Speech and Signal Processing 2013
DOI: 10.1109/icassp.2013.6637645
|View full text |Cite
|
Sign up to set email alerts
|

An effective, simple tempo estimation method based on self-similarity and regularity

Abstract: Tempo estimation is a fundamental problem in music information retrieval. It also forms the basis of other types of rhythmic analysis such as beat tracking and pattern detection. There is a large body of work in tempo estimation using a variety of different approaches that differ in their accuracy as well as their complexity. Fundamentally they take advantage of two properties of musical rhythm: 1) the music signal tends to be self-similar at periodicities related to the underlying rhythmic structure, 2) rhyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The proposed method schr1 was compared with the best performing algorithms [24,25,26,27] 4,5 discussed in [5] and a baseline method schr0 using the same five datasets, with the aforementioned improved ground truth. 6 The baseline schr0 consists of just the pulse estimation part described above, but without the SNM82-based octave correction.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The proposed method schr1 was compared with the best performing algorithms [24,25,26,27] 4,5 discussed in [5] and a baseline method schr0 using the same five datasets, with the aforementioned improved ground truth. 6 The baseline schr0 consists of just the pulse estimation part described above, but without the SNM82-based octave correction.…”
Section: Discussionmentioning
confidence: 99%
“…Because the time complexity of computing SNML is quadratic, we prefer smaller L. We found that the value determined for GTZAN, L = 82, represents a good tradeoff between correlation and runtime behavior. To compute the linear regression with WEKA [22], we use the combined five datasets [7,9,3,23,14] also used in [5], but a ground truth improved by Percival. The resulting regression for the rough perceived tempo estimate TO is given by:…”
Section: Estimating the Tempo Octavementioning
confidence: 99%
See 3 more Smart Citations